As sementes do axé vão à escola: desafios das crianças do candomblé junto ao processo de escolarização - Jesus, Alexandro dos Santos (Universidade Federal Rural do Semi-Árido, 2019)
The present work deals with an Afrodescendent sociocultural analysis of the children of the Terreiro de candomblé Kwê Ezin Azirí Dolá located in the Municipality of Areia Branca / RN. The Work also inserts itself into the very memory and life story of the narrator-researcher, as a participant in the African matrix religion. It seeks to reconstruct the memories of Terreiro's children. It allows to bring the voices of these subjects, their bonds, affections that create a sense of belonging, of identity and ancestrality. It presents candomblé as a symbolic place of rituals and rituals, vibrations, sensations, based on the individual and collective experiences of its members. The research aims to: Understand the main implications of the prejudice suffered by the children of Terreiro Kwê Ezin Azirí Dolá in the schools of Areia Branca / RN. As specific objectives we highlight: Identify what motivates the expressions of prejudice against the children of the terreiro; Analyze how children react to this prejudice in their experience within the school and in the various spaces of the city in which they live; reflect the actions taken by the school to combat this type of discrimination. In this sense, the methodology used in the research is qualitative in the bibliographic modality, anchoring itself in the life stories and memories of Candomblé children, using the (auto) biographical method. In order to understand the (auto) biography we use as theoretical methodological input the authors: Josso (2010), Passegi (2003). To understand the processes and mechanisms of prejudice we have as a source: Oliveira (2016), Arruda (2008) and Munanga (1996). A work that establishes a dialogue with the religion of candomblé, a space of learning in which daily knowledges / practices based on the construction, formation and resignification of Afrodescendant ancestry.
Monografia
Keywords: Educação para as relações étnico-raciais; Kwê Ezin Azirí Dolá; Expressões de preconceito; Candomblé; Ancestralidade; Education for racial Ethnicic relations; Candomblé; Prejudice expressions; Ancestry; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO RURAL